Comparison of different collection methods for reported adverse events following pandemic and seasonal influenza vaccination. Issue 34 (25th July 2016) - Kemmeren, Jeanet; Honsbeek, Maaike; Dijkstra, Frederika; de Lange, Marit; van der Maas, Nicoline; Smallenburg, Ronald; Koppeschaar, Carl; van der Hoek, Wim
Highlights: Recruitment through GPs is representative for the target group of influenza vaccination. Recruitment via internet is suitable when national representative information is needed. For pandemic vaccine safety monitoring a combination of both approaches is recommended. Abstract: Background: During the 2009/2010 season, information on adverse events after administration of seasonal and pandemic influenza vaccines was collected by different active surveys in the Netherlands. In the present paper, we compared data from a paper-based questionnaire with data from a web-based questionnaire with respect to outcomes and target population, in order to guide future influenza vaccine safety monitoring. Methods: The paper-based survey collected data from patients who attended primary care practices in the province of Utrecht for influenza vaccination. The web-based survey recruited participants from the general population all provinces of the Netherlands. To analyze the association between study approach and the reported local and systemic adverse events, a generalized estimation equation model was applied. We adjusted for age, gender, comorbidity, previous vaccination and socio-economic status score. Results: No significant differences were found between the two studies approaches in reporting local reactions (OR: 0.98, 95% CI 0.88–1.10) and systemic AEs (OR: 1.12, 95% CI 0.99–1.27). There were important differences in the age groups that responded. The elderly were more represented in the paper-based survey where participants were recruited via GPs (79% ⩾ 60 years) compared to 37% in the web-based survey where participants were recruited via internet. Conclusion: The paper-based survey with recruitment of participants through GPs is more representative for the target group of influenza vaccination compared to the web-based survey with recruitment of participants via internet. A web-based approach with recruitment of participants via internet seems more suitable for situations where information about adverse events on a national level is desirable. We recommend to recruit participants for a web-based survey during mass vaccinations sessions by GPs to comply with the recommendations of the European Centre for Disease Prevention Control.